Local and regional re-establishment of cellular immunity during curative antibiotherapy of murine Mycobacterium ulcerans infection - Martins, Teresa G. (2012)
BACKGROUND: Buruli ulcer (BU) is a neglected necrotizing disease of the skin, subcutaneous tissue and bone, caused by Mycobacterium ulcerans. BU pathogenesis is associated with mycolactone, a lipidic exotoxin with cytotoxic and immunosuppressive properties. Since 2004, the World Health Organization recommends the treatment of BU with a combination of rifampicin and streptomycin (RS). Histological analysis of human tissue samples suggests that such antibiotic treatment reverses the mycolactone-induced local immunosuppression, leading to increased inflammatory infiltrations and phagocytosis of bacilli. METHODOLOGY/PRINCIPAL FINDINGS: We used a mouse model of M. ulcerans footpad infection, followed by combined RS treatment. Time-lapsed analyses of macroscopic lesions, bacterial burdens, histology and immunohistochemistry were performed in footpads. We also performed CFU counts, histology and immunohistochemistry in the popliteal draining lymph nodes (DLN). We observed a shift in the cellular infiltrates from a predominantly neutrophilic/macrophagic to a lymphocytic/macrophagic profile in the infected footpads of antibiotic-treated mice. This shift occurred before the elimination of viable M. ulcerans organisms, which were ultimately eradicated as demonstrated by the administration of dexamethasone. This reduction of bacillary loads was accompanied by an increased expression of inducible nitric oxide synthase (NOS2 or iNOS). Predominantly mononuclear infiltrates persisted in the footpads during and after treatment, coincident with the long persistence of non-viable poorly stained acid-fast bacilli (AFB). We additionally observed that antibiotherapy prevented DLN destruction and lymphocyte depletion, which occurs during untreated experimental infections. CONCLUSIONS/SIGNIFICANCE: Early RS treatment of M. ulcerans mouse footpad infections results in the rapid elimination of viable bacilli with pathogen eradication. However, non-viable AFB persisted for several months after lesion sterilization. This RS regimen prevented DLN destruction, allowing the rapid re-establishment of local and regional cell mediated immune responses associated with macrophage activation. Therefore it is likely that this re-establishment of protective cellular immunity synergizes with antibiotherapy.